Sensitivity and specificity of rapid influenza testing of children in a community setting - Stebbins, Samuel (Blackwell Publishing Ltd, 2010)

(untitled) (Influenza Other Respir Viruses)
Please cite this paper as: Stebbins et al. (2011) Sensitivity and specificity of rapid influenza testing of children in a community setting. Influenza and Other Respiratory Viruses 5(2), 104–109. Introduction  Rapid influenza testing (RFT) allows for a rapid point‐of‐care diagnosis of influenza. The Quidel QuickVue(®) Influenza A+B test (QuickVue) has a reported manufacturer’s sensitivity and specificity of 73% and 96%, respectively, with nasal swabs. However, investigators have shown sensitivities ranging from 22% to 77% in community settings. Methods  The QuickVue rapid influenza test was evaluated in a population of elementary (K‐5) school children, using testing in the home, as part of the Pittsburgh Influenza Prevention Project during the 2007–2008 influenza season. The QuickVue test was performed with nasal swab in full accordance with package instructions and compared with the results of nasal swab semi‐quantitative RT‐PCR. Results  Sensitivity of the QuickVue was found to be 27% in this sample. There was no statistically valid correlation between the semi‐quantitative PCR result and the QuickVue result. Conclusions  This study is consistent with the low sensitivity of the QuickVue test also reported by others. Viral load, technique, and the use of nasal swabs were examined as contributing factors but were not found to be explanations for this result. Community testing includes patients who are on the lower spectrum of illness which would not be the case in hospital or clinic samples. This suggests that RFT is less sensitive for patients at the lower spectrum of illness, with less severe disease.